El vértigo de la superficie en los muros de Tomás Harris (Altre Modernità, 2021)
With this article we tried to focus our reading upon the poems that composeChilean writer Tomás Harris’ La vida a veces toma la forma de los muros (a sectionincluded in his 1992 work Cipango). After considering the texts depending on theirorder of appearance, we intended to identify those changes experienced by the imageof the wall and its relation with the lyrical subjects. Actually, the evident relevance of thewall affects not only the work themes, but also the verbal form itslef. This proceedingapproached us to a variety of impressions that could promote an existential perspectiveof wide reach, in addition to agreeing with other critical contributions. Thanks to thesupport of the thinking of authors like Deleuze, Guattari, and Sartre, among others, werealised that, starting from the wall element, a series of manifestations happens byquestioning the notion of human perception and consciousness.
Keywords: Poesía chilena; Tomás Harris; muro